Should lymphadenectomy be recommended in radical surgery of intrahepatic cholangiocarcinoma patients? A retrospective study - Ruoyu Zhang; Dayong Cao; Min Yang; Jiajun Zhang; Feng Ye; Ning Huang; Mei Liu; Bo Chen; Liming Wang (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Intrahepatic cholangiocarcinoma (ICC) is an extremely deadly cancer with high recurrence incidence, particularly in patients with lymph node metastasis (LNM). The necessity of lymphadenectomy including lymph node biology (LNB) and dissection (LND) during ICC radical surgery remains debate. Methods We retrospectively analyzed the patients diagnosed with ICC and underwent radical surgery at the Cancer Hospital of the Chinese Academy of Medical Sciences from 2012 to 2023. Results A total of 308 ICC patients were involved in this study. pLNM+ group had poorer OS (P < 0.0001) and poorer DFS (P < 0.0001) compared with pLNM− group. Compared to the LN− group, LN+ group exhibited worse OS (P = 0.038) and worse DFS (P = 0.003). After PSM and IPTW, compared with LN− group, LNB exhibited longer operation time (IPTW: P = 0.0024) and longer hospitalization days (IPTW: P = 0.0112) with no significant differences in complications, DFS, and OS. Compared with LN− group, LND group had no better DFS and OS, only more complications (IPTW: P = 0.0191), longer operation time (all P < 0.001), higher risk of bleeding (all P < 0.05), transfusion (IPTW: P = 0.014) and longer hospitalization days (IPTW: P = 0.0044). Compared with LNB group, LND had longer operation time (P = 0.0227), higher risk of bleeding (P = 0.017) and transfusion (P = 0.0321), and more postoperative complications (P = 0.0425), with no difference in DFS and OS. Conclusion Lymphadenectomy does not necessarily provide long-term survival or recurrence benefits. LND only achieves the effect of LNB while negatively affects postoperative recovery without survival benefit for ICC patients. LNB can be performed for accurate pathological staging while not all patients may require LND based on their specific circumstances.